Pengaruh Edukasi Media Booklet Sindrom Geriatri Terhadap Dukungan Sosial Keluarga Lansia Di Wilayah Kelurahan Bareng Kota Malang - Hafifa, Risma; Suprajitno; Marsaid; Subekti, Imam (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: To identify the influence of media education booklet geriatric syndrome on the social support of elderly families in the area of Kelurahan Bareng Kota Malang. Methods: The research design uses quasi eksperimental methods with Pre Post Test Design with Two Groups. The sampling method used purposive samplings with 60 respondents divided into two groups. Results: The results showed that rhe average score of social family support before intervention was 44,73 (mid category), while the average score after the intervention was 65,47 (high category), and the results obtained were p value 0,000 (p value 0,000 < a 0,05), meaning that there is a effect of education with geriatric syndrome booklet for increase elderly’s family social support. Conclusion: Education with geriatric syndrome booklet can be used to increase elderly’s family social support.